2022
DOI: 10.1371/journal.pmed.1003884
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric interventions and pregnancy outcomes during the COVID-19 pandemic in England: A nationwide cohort study

Abstract: Background The COVID-19 pandemic has disrupted maternity services worldwide and imposed restrictions on societal behaviours. This national study aimed to compare obstetric intervention and pregnancy outcome rates in England during the pandemic and corresponding pre-pandemic calendar periods, and to assess whether differences in these rates varied according to ethnic and socioeconomic background. Methods and findings We conducted a national study of singleton births in English National Health Service hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
3
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 30 publications
5
49
3
3
Order By: Relevance
“…There is some evidence that overall rates of perinatal mental health disorders increased internationally during the pandemic, including anxiety and depression, with links to the modification of maternity services ( Fan et al, 2021 ). We were unable to assess any impact of the changes we observed on outcomes for women and babies, but in terms of interventions and outcomes, in England one study has reported evidence of increased rates of obstetric intervention, including induction and Caesarean section, but little evidence of impact on adverse outcomes ( Gurol-Urganci et al, 2022 ). The impact on maternity staff was also beyond the scope of the surveys reported here, but is important to consider ( Horsch et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence that overall rates of perinatal mental health disorders increased internationally during the pandemic, including anxiety and depression, with links to the modification of maternity services ( Fan et al, 2021 ). We were unable to assess any impact of the changes we observed on outcomes for women and babies, but in terms of interventions and outcomes, in England one study has reported evidence of increased rates of obstetric intervention, including induction and Caesarean section, but little evidence of impact on adverse outcomes ( Gurol-Urganci et al, 2022 ). The impact on maternity staff was also beyond the scope of the surveys reported here, but is important to consider ( Horsch et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the effect modification by SES was not assessed in the aforementioned studies. [19][20][21][22] Within the published literature, single-center 45,51,[53][54][55] and national [56][57][58][59][60] studies have reported conflicting evidence in relation to perinatal outcomes during the COVID-19 pandemic. In a metaanalysis, Yang et al examined the influence of COVID-19 restrictions on maternal and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…( 15 , 16 ) Whilst the figures differ between various studies, maternal COVID-19 may be associated with increased risk of preeclampsia, delivery by caesarean section, preterm birth and stillbirth. ( 17 , 18 , 19 , 20 , 21 ) There was a stronger association with the latter during the period when the Delta (SARS-CoV-2 B.1.617.2) variant was predominant compared to the pre-Delta period. ( 22 ) The caveat is that not all mothers were tested for infection and many individuals were asymptomatic.…”
Section: Covid-19 Pandemicmentioning
confidence: 93%
“…There is limited literature to suggest that maternal COVID-19 has additional adverse effects in neonates apart from those related to prematurity. ( 20 , 21 , 22 , 23 )…”
Section: Covid-19 Pandemicmentioning
confidence: 99%